Functional mapping of the molluscan brain guided by synchrotron X-ray tomography - Michael Crossley; Anna Simon; Shashidhara Marathe; Christoph Rau; Arnd Roth; Vincenzo Marra; Kevin Staras (Proceedings of the National Academy of Sciences, 2025)
Molluscan brains are composed of morphologically consistent and functionally interrogable neurons, offering rich opportunities for understanding how neural circuits drive behavior. Nonetheless, detailed component-level CNS maps are often lacking, total neuron numbers are unknown, and organizational principles remain poorly defined, limiting a full and systematic characterization of circuit operation. Here, we establish an accessible, generalizable approach, harnessing synchrotron X-ray tomography, to rapidly determine the three-dimensional structure of the multimillimeter-scale CNS of Lymnaea . Focusing on the feeding ganglia, we generate a full neuron-level reconstruction, revealing key design principles and revising cell count estimates upward threefold. Our atlas uncovers the superficial but also nonsuperficial ganglionic architecture, reveals the cell organization in normally hidden regions—ganglionic “dark sides”—and details features of single-neuron morphology, together guiding targeted follow-up functional investigation based on intracellular recordings. Using this approach, we identify three pivotal neuron classes: a command-like food-signaling cell type, a feeding central pattern generator interneuron, and a unique behavior-specific motoneuron, together significantly advancing understanding of the function of this classical control circuit. Combining our morphological and electrophysiological data, we also establish a functional CNS atlas in Lymnaea as a shared and scalable resource for the research community. Our approach enables the rapid construction of cell atlases in large-scale nervous systems, with key relevance to functional circuit interrogation in a diverse range of model organisms.